2021
DOI: 10.1088/1755-1315/761/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acridine Orange in Promoting Growth and Physiological Characteristics of Fragaria Ananassa Duch Under Salinity Stress in Vitro

Abstract: This experimental were conducted out at plant tissue culture lab., Center of Desert studies to test the effect of four concentrations of Acridine Orange viz., 0, 10, 50 and 100mM L−1 under four levels of salinity viz., 0, 30, 60 and 90 mM NaCl L−1 on some phenological traits including: leaves number, branches number, plant length and fresh weight. Membrane stability index and electrolytic leakage also were in vitro measured. The experiment was factorial and arranged in a complete randomized design (CRD) with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
3
2
0
Order By: Relevance
“…In addition, the role of humic acid (Table 3) leads to an increase in the amount of chlorophyll, which encourages the production of large quantities of carbohydrates, which are used in the various vital activities of the plant as shown in Table (7), this led to the improvement of all vegetative and root characteristics of fig seedlings and the absorption of a greater amount of nutrients from the soil, and this is consistent with what was stated by [16,17,18,19].…”
Section: Discussion Of Vegetative Root and Chemical Characteristicssupporting
confidence: 87%
“…In addition, the role of humic acid (Table 3) leads to an increase in the amount of chlorophyll, which encourages the production of large quantities of carbohydrates, which are used in the various vital activities of the plant as shown in Table (7), this led to the improvement of all vegetative and root characteristics of fig seedlings and the absorption of a greater amount of nutrients from the soil, and this is consistent with what was stated by [16,17,18,19].…”
Section: Discussion Of Vegetative Root and Chemical Characteristicssupporting
confidence: 87%
“…In addition to the role of humic acid in maintaining soil moisture and aeration, which is reflected in the formation of a strong root system capable of absorbing nutrients and then stimulating vegetative growth [17], the reason for the increase in the nutrients content of the branches (table 5,6,7) may be due to the role of organic fertilizer and humic acid in increasing the permeability of cell membranes, which leads to facilitating the transfer of nutrients and thus increasing the efficiency of the plant to absorb and accumulate nutrients in the branches [18]. This is consistent with what was stated by Prajapati and Modi [19] and Kelley and Khalaf [20]and [21].…”
Section: Total Potassium Percentage In Branches (%)supporting
confidence: 86%
“…[17] reported that the acidity in fruits decreased in organically grown plants or plants that were fed adequate integrated nutrition. Poultry manure contains a good the proportion nitrogen and phosphorus, which leads to an increase in vegetative growth through an increase in the formation of proteins, and nucleic acids,the building of protoplasm, and efficiency in carbon metabolism, and the consequent increase in manufactured compounds and an increase in the percentage of dissolved solids [18] These results agreed with [19,20,21,22]…”
Section: Fruit Content Of Nitrates (Mg 100g-1 Dry Weight)supporting
confidence: 70%